2001
DOI: 10.1007/978-3-322-83021-0_1
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Electrophoresis in the Development of Recombinant Protein Biopharmaceuticals

Abstract: The understanding of the physicochemical properties of proteins in solution is required to understand the separations taking place in the capillary. For example, during isoelectric focusing, it is important to ensure the lack of protein precipitation during fOCUSing and mobilization otherwise artifacts occur and the true resolution of charge variants is not achieved. Similarly, buffer conditions, including additives, composition of buffer, and pH can influence the resolution of product variants. With diligent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 99 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…The possibilities for using CE to separate recombinant proteins in biopharmaceuticals were discussed recently in a specialized review [171]. Also, see the specialized review in this issue.…”
Section: Recombinant Proteinsmentioning
confidence: 99%
“…The possibilities for using CE to separate recombinant proteins in biopharmaceuticals were discussed recently in a specialized review [171]. Also, see the specialized review in this issue.…”
Section: Recombinant Proteinsmentioning
confidence: 99%
“…Authors from Genetech have reported [25] implementation of routine QC methods into their QA laboratories for batch release. Specific application include [25] protein content, hetrogeneity studies, peptide digest analysis as a characterisation tool and carbohydrate determinations.…”
Section: Pharmaceutical Analysismentioning
confidence: 99%
“…Authors from Genetech have reported [25] implementation of routine QC methods into their QA laboratories for batch release. Specific application include [25] protein content, hetrogeneity studies, peptide digest analysis as a characterisation tool and carbohydrate determinations. Workers from Medimmune reported [26] the optimization, validation, and use of capillary gel electrophoresis for quality control testing of Synagis (R), a monoclonal antibody.…”
Section: Pharmaceutical Analysismentioning
confidence: 99%
“…The role of CE as analytical tool for recombinant proteins has been extensively reviewed [132][133][134][135][136]. One major application is the characterization of glycoprotein variants [137,138].…”
Section: Capillary Electrophoresismentioning
confidence: 99%